Rock in high heels: a look through the women's role in Portuguese rock music - Martins, Ana (2019)
Traditionally rock music universe in our societies has been linked to men. In other words, many people still think about rock musicians, journalists, music critics, and many other music professionals as men. Some individuals even though a woman making rock music for a living was something weird or even disrespectful. This scenario still happens today all over the world and Portugal is no exception to that. However, we can't talk about the history of rock'n'roll music without mention the contribution of women. Although just a few, in the beginning, women have been leaving a growing mark in world's rock music and are becoming more independent musically. Because of all this, it's very important to think over and discuss the gender issues in Portuguese rock music and look at women's role in this sphere.